Physical Process Controlling the Surface Bacterial Community Composition in the Ulleung Basin of East Sea - Kim, Hyo-Ryeon; Lim, Jae-Hyun; Kim, Ju-Hyoung; Thangaraj, Satheeswaran; Kim, Il-Nam (Frontiers in Marine Science, 2022)
Although environmental drivers have been shown to shape the abundance and distribution of bacterial communities in the East Sea, the effects of physical processes have not been directly studied. Here we examine the influences of water mass mixing (in-summer) and eddy circulation (in-winter) on surface bacterial communities of the Ulleung Basin (UB), East Sea, based on the metagenomic approach. Overall, 490,087 operational taxonomic units (OTU) were identified from five stations, and prokaryotic abundances were observed to be dominated at all stations in both seasons. Among prokaryote most OTU was affiliated with Proteobacteria, Cyanobacteria, Flavobacteria, and Actinobacteria during both summer and winter. Results showed that bacterial communities differed with water masses (Changjiang, Tsushima, and North Korean Surface water) and eddy circulation, displayed a strong correlation with environmental variables, suggesting specific bacterial communities response with specific seasonal physicochemical parameters. Our investigation represents that along with distance and environment, advection shapes the composition of bacterial communities in the UB, helping us to better understand the physical cues related to biological composition in the East Sea. However, further studies are needed to ascertain the role of microbial functional genes along with the advection of oceanographic process in the East Sea to understand better the regional biogeochemical processes.